2018
DOI: 10.1002/dvdy.1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental roles of microglia: A window into mechanisms of disease

Abstract: Microglia are engineers of the CNS both in health and disease. In addition to the canonical immunological roles of clearing damaging entities and limiting the spread of toxicity and death, microglia remodel the CNS throughout life. While they have been extensively studied in disease and injury, due to their highly variable functions, their precise role in these contexts still remains uncertain. Over the last decade we have greatly expanded our understanding of microglial function, including their essential hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 280 publications
(576 reference statements)
2
22
0
1
Order By: Relevance
“…Microglia are the resident immunocytes of the CNS; unlike other tissue macrophages, they persist for the life of the organism with negligible turnover rates at steady state (Tay et al, 2016;Anderson and Vetter, 2019). Microglia are instrumental in the maintenance of biochemical homeostasis, neuronal circuit maturation during development, and experience-dependent remodeling of neuronal circuits in the adult brain (Szepesi et al, 2018;Anderson and Vetter, 2019;Illes et al, 2019). The cellular processes of quiescent or ''resting'' microglia are highly mobile (extension and withdrawal) by scanning the environment for disruptions of brain homeostasis (Davalos et al, 2005).…”
Section: Microglial and Astroglial Functions; Cell Death And Prolifermentioning
confidence: 99%
“…Microglia are the resident immunocytes of the CNS; unlike other tissue macrophages, they persist for the life of the organism with negligible turnover rates at steady state (Tay et al, 2016;Anderson and Vetter, 2019). Microglia are instrumental in the maintenance of biochemical homeostasis, neuronal circuit maturation during development, and experience-dependent remodeling of neuronal circuits in the adult brain (Szepesi et al, 2018;Anderson and Vetter, 2019;Illes et al, 2019). The cellular processes of quiescent or ''resting'' microglia are highly mobile (extension and withdrawal) by scanning the environment for disruptions of brain homeostasis (Davalos et al, 2005).…”
Section: Microglial and Astroglial Functions; Cell Death And Prolifermentioning
confidence: 99%
“…Both short-and long-term CNTF treatments further elevated the expression of genes involved in innate and adaptive immune systems, interferon, NF-kB, Jak-STAT, GPCR and MAPK signaling. Recent studies have shown a rapid and persistent activation of microglia in degenerating retinas, accompanied by significantly enhanced chemokine and cytokine gene upregulations [39][40][41][42] . Part of our RNA-seq data showing the uptick of immune system www.nature.com/scientificreports www.nature.com/scientificreports/ and chemokine gene expression may reflect microglia activities in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic blood supply disturbances of nervous tissue and other hypoxic states are the most common pathological condition of the central nervous system (CNS). Hypoxia of brain significantly reorganizes the CNS, changes the integrative-starting activity of neurons and leads to the formation of qualitatively new pattern of interaction between individual brain structures, and in the case of de-compensation of adaptation mechanisms, triggers a chain of pathological processes resulting in progressive neurological and cognitive disorders, including the development of encephalopathy [1][2][3][4][5][6]. Pharmacological action of existing neuroprotective agents consists mainly in protection or modulation of functions of mature cells of nervous tissue surviving in the pathology.…”
Section: Introductionmentioning
confidence: 99%
“…12,83±2,62 # 7,24±2,88 # 2,26±0,93 0,83±0,37 1,26±0,35 0,00±0,00 1,72±0,834 16,22±1,92 # 10,69±2,55 2,62±0,71 0,67±0,21 0,88±0,44 0,00±0,00 1,24±0,62 In the second period of the study(2-3 minute) 1 9,48±2,11 2,43±1,21 2,67±0,55 2,45±0,71 1,22±0,76 0,63±0,32 0,60±0,60 2 32,36±3,74 16,62±2,03 6,72±1,16 3,16±0,33 2,92±0,47 1,38±0,71 0,00±0,00 3 14,16±3,05# 9,39±1,67# 2,36±0,42# 1,78±0,54 1,99±0,50 0,56±0,55 0,72±0,37 4 12,21±2,42 6,16±2,25 2,93±1,12 0,66±0,12 1,31±0,62 0,83±0,51 0,89±0,52…”
unclassified